Extracellular Vesicles in Chagas Disease: A New Passenger for an Old Disease - de Pablos Torró, Luis M.; Retana Moreira, Lissette; Osuna, Antonio (Frontiers in Microbiology, 2018)
Extracellular vesicles (EVs) are small lipid vesicles released by prokaryotic and eukaryotic cells containing nucleic acids, proteins, and small metabolites essential for cellular communication. Depending on the targeted cell, EVs can act either locally or in distant tissues in a paracrine or endocrine cell signaling manner. Released EVs from virus-infected cells, bacteria, fungi or parasites have been demonstrated to perform a pivotal role in a myriad of biochemical changes occurring in the host and pathogen, including the modulation the immune system. In the past few years, the biology of Trypanosoma cruzi EVs, as well as their role in innate immunity evasion, has been started to be unveiled. This review article will present findings on and provide a coherent understanding of the currently known mechanisms of action of T. cruzi-EVs and hypothesize the implication of these parasite components during the acute and chronic phases of Chagas disease.